DNA methylation and breast tumor clinicopathological features: The Western New York Exposures and Breast Cancer (WEB) study. Issue 9 (1st September 2016) - Callahan, Catherine L.; Wang, Youjin; Marian, Catalin; Weng, Daniel Y.; Eng, Kevin H.; Tao, Meng-Hua; Ambrosone, Christine B.; Nie, Jing; Trevisan, Maurizio; Smiraglia, Dominic; Edge, Stephen B.; Shields, Peter G.; et al.
ABSTRACT: We evaluated the association between methylation of 9 genes, SCGB3A1, GSTP1, RARB, SYK, FHIT, CDKN2A, CCND2, BRCA1, and SFN in tumor samples from 720 breast cancer cases with clinicopathological features of the tumors and survival. Logistic regression was used to estimate odds ratios (OR) of methylation and Cox proportional hazards models to estimate hazard ratios (HR) between methylation and breast cancer related mortality. Estrogen receptor (ER) and progesterone receptor (PR) positivity were associated with increased SCGB3A1 methylation among pre- and post-menopausal cases. Among premenopausal women, compared with Stage 0 cases, cases of invasive cancer were more likely to have increased methylation of RARB (Stage I OR = 4.7, 95% CI: 1.1–19.0; Stage IIA/IIB OR = 9.7, 95% CI: 2.4–39.9; Stage III/IV OR = 5.6, 95% CI: 1.1–29.4) and lower methylation of FHIT (Stage I OR = 0.2, 95% CI: 0.1–0.9; Stage IIA/IIB OR = 0.2, 95% CI: 0.1–0.8; Stage III/IV OR = 0.6, 95% CI: 0.1–3.4). Among postmenopausal women, methylation of SYK was associated with increased tumor size (OR = 1.7, 95% CI: 1.0–2.7) and higher nuclear grade (OR = 2.0, 95% CI 1.2–3.6). Associations between methylation and breast cancer related mortality were observed among pre- but not post-menopausal women. Methylation of SCGB3A1 was associated with reduced risk of death from breast cancer (HR = 0.41, 95% CI: 0.17–0.99) as was BRCA1 (HR = 0.41, 95% CI: 0.16–0.97). CCND2 methylation was associated with increased risk of breast cancer mortality (HR = 3.4, 95% CI: 1.1–10.5). We observed differences in methylation associated with tumor characteristics; methylation of these genes was also associated with breast cancer survival among premenopausal cases. Understanding of the associations of DNA methylation with other clinicopathological features may have implications for prevention and treatment.